2019
DOI: 10.21203/rs.2.10157/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and risk factors of chronic kidney disease and diabetic kidney disease in a central Chinese urban population: a cross-sectional survey

Abstract: Background : This study was conducted to evaluate and update the current prevalence of and risk factors for chronic kidney disease (CKD) and diabetic kidney disease (DKD) in China. Methods : A total of 5231 participants were randomly recruited for this study. CKD and DKD were defined according to the combination of the estimated glomerular filtration rate (eGFR) and the presence of albuminuria and diabetes. Participants completed a questionnaire assessing lifestyle and relevant medical history, and blood and u… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…Escalating CKD incidence among diabetic patients, as well as increasing CKD-induced mortality merit careful attention [4,27,28]. Coexistent CKD was noted in 16.8% to 24.4% of the Asian diabetic population, whereas 43.8% of diabetes with microvascular complications reported eGFR below 60 ml/min [29][30][31]. Similarly, our high-risk patients exhibited a soaring prevalence of CKD (41.1%), which elaborated higher baseline prescription of RAAS inhibitor (89.8%) and statin (67.1%) compared to the Vietnamese subpopulation of the DiabCare study (46.8% and 40.3%, respectively) [32].…”
Section: Discussionmentioning
confidence: 99%
“…Escalating CKD incidence among diabetic patients, as well as increasing CKD-induced mortality merit careful attention [4,27,28]. Coexistent CKD was noted in 16.8% to 24.4% of the Asian diabetic population, whereas 43.8% of diabetes with microvascular complications reported eGFR below 60 ml/min [29][30][31]. Similarly, our high-risk patients exhibited a soaring prevalence of CKD (41.1%), which elaborated higher baseline prescription of RAAS inhibitor (89.8%) and statin (67.1%) compared to the Vietnamese subpopulation of the DiabCare study (46.8% and 40.3%, respectively) [32].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, when uric acid is present in the cytoplasm of cells or in the acidic/hydrophobic environment of atherosclerotic plaques, it is converted to a pro-oxidant, and it promotes oxidative stress, including cardiovascular disease through this mechanism, participating in the pathophysiology of human disease [ 21 ]. Recent studies reported that hyperuricemia is an independent predictor of CKD [ 22 , 23 ]. Uric acid concentration is an independent risk factor for kidney failure in earlier stages of CKD and has a J-shaped relationship with all-cause mortality in CKD [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…DKD has been the most common cause of ESRD in Western countries, and numerous risk factors have been identified for its progression, including but not limited to older age, smoking, alcohol consumption, overweight/obesity, hyperglycemia, hypertension, dyslipidemia, and hyperuricemia [ 4 , 17 , 18 ]. However, even under strict control of body weight, blood glucose, and blood pressure, some patients still progress to ESRD.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had shown that dyslipidemia was a well-established risk factor for the renal impairment in diabetes; it is not only associated with the occurrence [ 2 , 10 , 19 ] but also the deterioration [ 4 , 11 ] of DKD. A cross-sectional study published in 2014 involving 13 countries reported the plasma lipid's contribution to the occurrence of DKD; hypertriglyceridemia significantly increased the risk of DKD, and high HDL-C was a protective factor [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation